Technological innovation and economic performance - Steil, Benn.; Victor, David G.; Nelson, Richard R.; Council on Foreign Relations (Princeton, N.J. : Princeton University Press, 2002)
Information technology accounts for over one-third of recent U.S. GDP growth and nearly two-thirds of corporate capital investment. ''The New Economy'' appears omnipresent, but little is actually known about its workings.This seminal volume brings together the research and critical thinking of many of the world's top macro and micro economists to provide a unique, multifaceted perspective. Through the use of detailed, up-to-date country and industry studies, this book provides the most authoritative and detailed analysis ever assembled into the causes of technological innovation and its relationship to economic performance. The country studies cover the United States, Japan, Germany, France, the United Kingdom, and the Nordic states. Nine industry studies examine the Internet, computers and semiconductors, banking, securities trading, venture capital, energy, agricultural biotechnology, pharmaceutical biotechnology, and automobiles.Commissioned and brought together for the research project by the world-renowned Council on Foreign Relations, the authors have produced one of the most important compendia in applied economics to be published in recent times.The contributors are Charles Calomiris, Ian Domowitz, Robert Evenson, Charles Fine, Robert Gordon, Richard Langlois, Josh Lerner, Markku Malkamäki, Patrick Messerlin, Joel Mokyr, David Mowery, Richard R. Nelson, Stephen Nickell, Gary Pisano, Adam Posen, Daniel Raff, Horst Siebert, Timothy Simcoe, Benn Steil, Michael Stolpe, John Van Reenen, David Victor, and Matti Virén.
Introduction and overview / Benn Steil, David G. Victor, and Richard R. Nelson -- Innovation in an historical perspective: tales of technology and evolution / Joel Mokyr -- The United States / Robert J. Gordon -- Japan / Adam S. Posen -- Germany / Horst Siebert and Michael Stolpe -- France / Patrick A. Messerlin -- The United Kingdom / Stephen Nickell and John Van Reenen -- The Nordic countries / Matti Virén and Markku Malkamaki -- The Internet / David C. Mowery and Timothy Simcoe -- Computers and semiconductors / Richard N. Langlois -- Banking and financial intermediation / Charles W. Calomiris -- Securities trading / Ian Domowitz and Benn Steil -- Venture capital / Josh Lerner -- Pharmaceutical biotechnology / Gary P. Pisano -- Agricultural biotechnology / Robert E. Evenson -- Electric power / David G. Victor -- Automobiles / Charles H. Fine and Daniel M.G. Raff.
Title from title screen.
Includes bibliographical references and indexes.
JSTOR
Keywords: Technological innovations -- Economic aspects -- Case studies; Industrial productivity -- Case studies; Innovations -- Aspect économique -- Études de cas; Productivité -- Études de cas; BUSINESS & ECONOMICS / Economics / General; Industrial productivity; Technological innovations -- Economic aspects; Internationaler Vergleich; Industrie; Wirtschaftsentwicklung; Technische Innovation; Computerindustrie; Internet; Hochtechnologiesektor; Industrielle Forschung; Innovationspolitik; Forschungs- und Technologiepolitik; Produktivität.; Wirtschaftswachstum; Nordeuropa; Grossbritannien; Frankreich; USA; Deutschland; Kraftfahrzeugindustrie; Elektrizitätswirtschaft.; Biotechnologie; Finanzmarkt; Technischer Fortschritt; Case studies